Related Factors of Teenage Pregnancy at Tharua Hospital, Phra Nakhon Si Ayutthaya Province - พงศ์พัฒนานนท์ วิวรรณ (Journal of Preventive Medicine Association of Thailand, 2018)
Teenage pregnancy is an important public health issue in Thailand as the rate of teenage pregnancy has increased substantially over the recent years. This research employs cross-sectional survey in order to study the contributing factors and effects of teenage pregnancy, particularly for physical and mental care, as well as family support. The study also aims to analyze the relationship between individual factors, including age, occupation and educational attainment, and effects on personal care during pregnancy, teenaged mothers’ mental health problems and family support. The survey used a sample size of 53 teenaged mothers treated in the Tharua hospital during August to October 2015. The statistical analysis included percentage, mean, the T-Test and analysis of variance (ANOVA). The results showed that 66 percent of sample sizes are students, 86.8 percent are first pregnancy, 54.72 percent are in first trimester of pregnancy, 84.5 percent are married, 90.6 percent have no abortion record or miscarriage, 73.6 percent were unintended pregnancy, 50.9 percent were living in two-parent families. Taking the effects of teenage pregnancy on personal care into account, people have a good prenatal care, low emotional crisis and adequate family support. The study found that individual factors have no strong relationship with teenage pregnancy. On the other hand, pregnancy planning has an impact on mental health with statistical significance. Types of families also play a key role in support teenage pregnancy. In conclusion, the study found that teenage pregnancy whose parents are together can provide support to help families better than the parent do not live together. Research recommendations are therefore to promote family involvement in treatment for teenage pregnancy and promotefamily planning, contraception in teenage.